Niedoszłe polsko-niemieckie „Gesamtlösung” w roku 1939 a sprawa żydowska - Kornat, Marek (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
From October 1938 to March 1939, the German Nazi government was trying to achieve a “general solution” (Gesamtlösung) in the relations with Poland. Hitler wanted not only the incorporation of Gdańsk (Danzig) and extraterritorial connection to Eastern Prussia, but also to have Poland as a satellite state. The demands were not accepted by the Foreign Minister of Poland col. Beck. Many exhaustive studies on Polish-German relations were published in the last phase of peace (1938–1939), but there was no work on the role of the so called “Jewish problem” in the Nazi plans concerning Poland. The author of the article tries to prove that this question was an integral element of German negotiation strategy with Warsaw. There is no doubt that the Nazi government wanted to impose principally anti-Jewish collaboration on Poland. Fortunately, the project was rejected by the Polish government.
Keywords: Polska; Niemcy; sprawy żydowskie; konflikt 1939 roku; druga wojna światowa